PHYTOCHEMICAL SCREENING AND COMPARISON OF ANTIOXIDANT ACTIVITY OF WATER AND ETHANOL EXTRACT PROPOLIS FROM MALAYSIA - Usman, Umar Zayyanu; Abu Bakar, Ainul Bahiyah; Mohamed, Mahaneem (International Journal of Pharmacy and Pharmaceutical Sciences, 2016)
Objective: In an attempt to compare extraction yield, phytochemical screening, radical scavenging activity, and total phenolic and flavonoid contents of water extract propolis (WEP) and ethanol extract propolis (EEP) from Malaysia. Methods: Raw propolis was extracted using distilled water and ethanol at various concentrations (10-100%) and the extraction yields were presented in percentage. The phytochemical screening, radical scavenging activity, total phenols using Folin-Ciocalteu method and flavonoid using aluminum chloride method of WEP and EEP were determined. Results: Malaysian propolis extracted using 70% ethanol produced the highest extraction yield and had significantly higher radical scavenging activity as well as total phenolic and flavonoid contents compared to WEP. Conclusion: Malaysian propolis extract using 70% ethanol is potential to be developed as a good antioxidant agent. Keywords: Antioxidant, Extractions, Malaysian, Propolis, Phytochemical screening